Fracture of the proximal extremity of the tibia after anterior cruciate ligament reconstruction: case report() - de Oliveira Carneiro, Márcio (Rev Bras Ortop, 2015)
We report a rare condition that has been little described in the literature: a fracture of the proximal extremity of the tibia after anterior cruciate ligament reconstruction using an autologous patellar bone-tendon graft. In this report, we discuss the factors that predisposed toward this episode, the treatment and the evolution of the case after the surgical treatment.